2018
DOI: 10.9781/ijimai.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Textural Aspects for Arabic Handwritten Characters Recognition

Abstract: The purpose of the present paper is the recognition of handwritten Arabic characters in their isolated form. The specificity of Arabic characters is taken into consideration, each of the proposed feature extraction method integrates one of the two aspects: spatial and textural. In the first step, a modified Bitmap Sampling method is proposed, which converts the character's images into a binary Matrix and then constructs a Mask for each class. A matching rate is used between the input binary matrix and the mask… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The histograms are then concatenated to create a feature vector, which is fed into a neural network classifier. In the same regard, the paper (15) aimed to create a method that considers both the spatial and textural aspects of isolated Arabic handwritten character recognition. To extract features from the char-acter images, the authors suggested using local binary patterns (LBP) and a modified bitmap sampling technique.…”
Section: Related Workmentioning
confidence: 99%
“…The histograms are then concatenated to create a feature vector, which is fed into a neural network classifier. In the same regard, the paper (15) aimed to create a method that considers both the spatial and textural aspects of isolated Arabic handwritten character recognition. To extract features from the char-acter images, the authors suggested using local binary patterns (LBP) and a modified bitmap sampling technique.…”
Section: Related Workmentioning
confidence: 99%
“…A problem that has been widely studied is how to find the characteristic words of a document (e.g., [44][45][46][47]). ese characteristic words can be used, for instance, to implement keywordbased document search.…”
Section: Characteristic Words Of a Documentmentioning
confidence: 99%
“…Spatial and Textural Aspects for Arabic Handwritten Characters Recognition (Morocco), Boulid, et al purpose was the recognition of handwritten Arabic characters in their isolated form, and had 2.82% error rate [11].…”
Section: Eeg Signal Analysis Of Writing and Typing Between Adults Withmentioning
confidence: 99%